Perception of Halal Logo on Food and Beverage Products among Students (Aged 20-25 Years) - Arifin Noer, Bustanul (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2022)
Food is a necessity from every human being and part of the rights every human rights in Indonesia. Islam has arranged many things regarding halal and haram in the field food. Halal is a concept the rules of Islamic religious principles, which are used to declare something permitted or prohibited for consumption by Muslims on the basis of the Qur'an, Hadith, or Ijtihad. The purpose of this research is to find students who have a buying interest high in food and beverage products include a halal logo or without requires a halal label. Inside population this research is adolescents in East Java, while the number of successful samples a number of 120 respondents were processed with a purposive sampling method from total questionnaire distributed a total of 194 respondents. The results show that the perception of the halal logo is posed on the respondents' questions get a presentation that's quite high, that is, 49% of students have know and understand about logos Halal and the suitability of the logo according to the MUI.